A hierarchical latent variable model of leadership styles using PLS-SEM - Arshad, Azlin Shafinaz (Penerbit UTM, 2014)
The aim of this article is to propose second order hierarchical component models to analyze the two leadership styles (transformational leadership and transactional leadership) for technology-based SMEs. We adopted the two-stage approaches in partial least square-structural equation modelling to examine the appropriateness of hierarchical modelling for both leadership styles. The findings indicate that the conceptual properties of transformational leadership and transactional leadership are matched with reflective-formative type of second order hierarchical component models. In addition, the study offers an alternative avenue to those researchers who are intending to introduce hierarchical component models in modelling leadership styles